2021
DOI: 10.3390/geriatrics6020055
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for Nursing Home Residents with Dysphagia—A Scoping Review

Abstract: Oropharyngeal dysphagia is common in nursing home residents. The objective of this scoping review was to summarize and disseminate the findings from the literature on interventions for dysphagia in nursing home residents. Searches were conducted in four databases. The criteria for including the studies were nursing home residents, dysphagia, interventions, original research, published in English, Danish, Norwegian, or Swedish with no restriction placed regarding publication date. Excluded were literature revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…TMD as the sole form of intervention for dysphagia in RACFs has shown promise for improving body mass index [ 37 ]. The studies that produced this positive outcome provided TMDs for periods of 3 to 6 months [ 38 , 39 ], which indicates the need for longer-term implementation of TMDs for nutritional and oral intake effects to be observed.…”
Section: Discussionmentioning
confidence: 99%
“…TMD as the sole form of intervention for dysphagia in RACFs has shown promise for improving body mass index [ 37 ]. The studies that produced this positive outcome provided TMDs for periods of 3 to 6 months [ 38 , 39 ], which indicates the need for longer-term implementation of TMDs for nutritional and oral intake effects to be observed.…”
Section: Discussionmentioning
confidence: 99%
“…To be eligible for inclusion in this systematic review, studies had to meet the following criteria: (1) participants had a diagnosis of oropharyngeal dysphagia; (2) the study included non-invasive neurostimulation interventions aimed at reducing swallowing or feeding problems; (3) the study included a control group or comparison intervention group; (4) participants were randomly assigned to one of the study arms or groups; and (5) the study was published in English language.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Oropharyngeal dysphagia (OD) or swallowing problems is highly prevalent among stroke patients, people with progressive neurological diseases, patients with head and neck cancer, and in frail older persons [1,2]. Prevalence estimates of OD may vary depending on underlying medical diagnoses, but have been reported as high as 80% in stroke and Parkinson's disease [3], and 70% in oncological populations [4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, OD is particularly common among frail older people, being described by the European Society for Swallowing Disorders (ESSD) as a geriatric syndrome [ 6 ], usually presenting multiple age-related changes, like loss of muscle mass and sarcopenia [ 7 ]. Additionally, critical complications may arise from dysphagia, namely aspiration pneumonia [ 7 , 8 , 9 ], one of the most prominent death causes in older adults, associated with mortality rates up to 50% [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, OD is particularly common among frail older people, being described by the European Society for Swallowing Disorders (ESSD) as a geriatric syndrome [ 6 ], usually presenting multiple age-related changes, like loss of muscle mass and sarcopenia [ 7 ]. Additionally, critical complications may arise from dysphagia, namely aspiration pneumonia [ 7 , 8 , 9 ], one of the most prominent death causes in older adults, associated with mortality rates up to 50% [ 10 ]. Recently, a case report focused on OD and related pneumonia aspiration, following infection by SARS-CoV-19, and it concluded that the patient developed impaired pharyngolaryngeal sensation, mesipharyngeal contractile dysfunction and silent aspiration in the recovery phase [ 11 ], thus eliciting the need to early detect and prevent OD events.…”
Section: Introductionmentioning
confidence: 99%